Mitigating Devices to Save Face in Sellers and Buyers Communication in Bukittinggi Traditional Market - Widya Widya; Erika Agustiana (UIN Salatiga, 2023)
Due to their content and ways of expression, several speech acts have the potential to threaten the participant's face during an interaction. Mitigating devices can be employed to reduce the harmful effects of these face-threatening acts (FTAs). In this study, the researchers focused on interactions between sellers and buyers in the traditional market in Bukittinggi, West Sumatera, which makes use of the colloquial Minangkabau language. This descriptive qualitative research was aimed at investigating the mitigation functions that exist in buying and selling interactions. In addition, it sought to identify the different types of mitigation strategies used by participants. Research data was collected by recording the exchanges between sellers and buyers. To complete the data, a questionnaire was also handed out to Minangkabau-speaking sellers and buyers in Bukittinggi's traditional market. The data analysis technique used in this study was contextual analysis, which involved evaluating the data that had been collected, recognizing it, and classifying it using the dimensions of context. The result showed that the face of the interlocutor was protected in this purchasing and selling encounter using a variety of mitigating devices. The most commonly used mitigation device is indirect speech. Other techniques, including disclaimers, impersonal constructions, hedges, euphemisms, question tags, and apologies, were also found as mitigation devices used by communicators. The purpose of using these mitigation devices is to carry out mitigation functions such as self-defense, prevention, or repair. Both the buyer and the seller are capable of carrying out all of these functions.